Suture Sliding Technique for Arthroscopic Matrix-based Meniscus Repair - Sean Wei Loong Ho, M.B.B.S., M.Med. (Ortho.), F.R.C.S. (Ortho.).; Timothy Zhen Xin Tan; Wei Zhang, M.B.B.S., M.Med. (Ortho.).; T. Jegathesan, M.B.B.S., M.Med. (Ortho.)., F.R.C.S. (Ortho.).; Lester Teong Jin Tan, M.B.B.S., M.Med. (Ortho.)., F.R.C.S. (Ortho.).; Keng Thiam Lee, M.B.B.S., M.Med. (Ortho.), F.R.C.S. (Ortho.). (Arthroscopy Techniques)
Complex meniscal tears associated with poor meniscal quality can be challenging to repair. A robust repair configuration is required for a successful repair. Blood supply and adequate biology are also important factors to improve healing rates. Biological augmentation of a meniscus repair can be performed via orthobiologics or collagen-based matrices. The aim of this Technical Note is to describe a surgical technique of matrix insertion by sliding the matrix down sutures during arthroscopic matrix-based meniscus repair.